1997
DOI: 10.1021/jp972491o
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of DNA Base Trimers:  An Electrostatic Approach

Abstract: Triplexes involving major groove binding of a third oligomer to the DNA duplex structure have gathered much interest in recent years. The study of base trimer interactions in the gas phase is expected to provide useful information regarding orientational preferences and inherent stabilities. A recently developed electrostatic potential for intermolecular complexation (EPIC) model has been found to be quite useful for exploring the structures and energetics in base pairs [Gadre, S. R.; Pundlik, S. S. J. Phys. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…Similarly the Lewis acid properties of triel centers analyzed here may be explained in terms of EP. One can mention other important studies, as for example, on the role of EP in the hydratation process or on the stability of DNA dimers and trimers …”
Section: Resultsmentioning
confidence: 99%
“…Similarly the Lewis acid properties of triel centers analyzed here may be explained in terms of EP. One can mention other important studies, as for example, on the role of EP in the hydratation process or on the stability of DNA dimers and trimers …”
Section: Resultsmentioning
confidence: 99%
“…This interaction energy is minimized by rotating and translating the guest molecule such that the van der Waals surfaces of the guest and the host do not interpenetrate. The EPIC model was applied successfully to many systems such as DNA base dimers and trimers [86], hydration of crown ether [87] and stacked and H-bonded cytosine dimer [88]. Previous studies performed in our laboratory generally demonstrated striking similarities between the geometries obtained from ab initio and EPIC calculations.…”
Section: Use Of Molecular Electrostatic Potential For Probing Lone Pamentioning
confidence: 79%
“…This electrostatic picture brings out the reason why electron rich species interact attractively with π -deficient aromatic systems. Based on electrostatics and its topographical features, Gadre et al [85,86] developed a model several years' ago, named as electrostatic potential for intermolecular complexation (EPIC), which provides a simple tool for estimating the interaction energy and geometry of the weakly interacting molecular species. In this model, the interaction energies are calculated by summing the MESP driven point charges q A,i of the guest molecule multiplied with the electrostatic potential value of the host at the location of the point charge and vice versa.…”
Section: Use Of Molecular Electrostatic Potential For Probing Lone Pamentioning
confidence: 99%
“…The interactive energies of the multimers have been calculated with Hartree-Fock, 39 DFT, [40][41][42]43,44 methods, to be used to examine our RM1 BH . Fortunately, there exist some experimental trimerization energies estimated by analyzing mass spectral peak intensities in multicomponent mixtures.…”
Section: Some Multimers Among Base(s) And/or Amino Acid Residue(s)mentioning
confidence: 99%